2016
DOI: 10.15376/biores.11.2.3384-3396
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Activated Carbon from Pyrolyzed Rice Husk by Leaching out Ash Content after CO2 Activation

Abstract: To prepare activated carbons with a high porosity and low ash content from pyrolyzed rice husk, the method of KOH or K2CO3 solution leaching after CO2 activation was investigated. The effects of KOH or K2CO3 concentration and leaching time on the yield, ash content, and textural properties of the activated carbon were studied, and the activated carbon prepared under the best conditions was characterized. The results showed that the best leaching time was 1 h for KOH and K2CO3, and the best concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The use of the residues in preparation or production of a higher valued material as an alternative transforming waste in raw material. Recently, many studies have reported the production of activated carbon (AC) from residues such as: Rice husk, [6]; Green Coconut Shell, [7];Babassu coconut, [8];Mukah coal, [9]; Residues of babassu, [10]; Coffee waste, [11];Oil palm, [12], etc. Many studies have discussed great potential of lignocellulosic as a renewable feedstock for preparation of Activated Carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the residues in preparation or production of a higher valued material as an alternative transforming waste in raw material. Recently, many studies have reported the production of activated carbon (AC) from residues such as: Rice husk, [6]; Green Coconut Shell, [7];Babassu coconut, [8];Mukah coal, [9]; Residues of babassu, [10]; Coffee waste, [11];Oil palm, [12], etc. Many studies have discussed great potential of lignocellulosic as a renewable feedstock for preparation of Activated Carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The low surface area also can be attributed to the pore blockage on the adsorbent surface by the remaining chemical agent (Yunus et al 2020). Post-treatment via H3PO4 was unable to promote further deashing, which might be due to the insulating layer formation on the adsorbent surface (Li et al 2016;Peng et al 2018). This study shows that H3PO4 post-treatment affected the interior cell walls and the pore structure of activated carbon.…”
Section: Effect Of Deashing Treatment On the Surface Morphology Of Activated Carbonmentioning
confidence: 78%
“…The success of biomass conversion into activated carbon with high microporous structure depends on two main factors: creation of high surface area through the development of micropores and removal of ash content during the activation process. Li et al (2016) reported that increases in the specific surface area and pore volume were consistent with decreasing ash content. Thus, deashing is a crucial process for the conversion of lignocellulosic biomass into advanced functional activated carbon.…”
Section: Introductionmentioning
confidence: 92%
“…Ash produced when carbon is physically activated is the origin of impurities between carbon surfaces. The ability of activated carbon to absorb will decrease due to the high ash content 45,46 …”
Section: Resultsmentioning
confidence: 99%